2013
DOI: 10.1590/s0102-09352013000400019
|View full text |Cite
|
Sign up to set email alerts
|

Infusão contínua de morfina ou fentanil, associados à lidocaína e cetamina, em cães anestesiados com isofluorano

Abstract: RESUMOA técnica de analgesia multimodal, por meio da infusão contínua de fármacos, pode ser empregada para diminuir a incidência de sensibilização central durante a anestesia. Avaliaram-se as características cardiorrespiratórias, durante o procedimento de artroscopia de joelho, em cães anestesiados com isofluorano e monitorados por meio do índice biespectral, submetidos à infusão contínua de morfina ou fentanil, associada à lidocaína e cetamina. Utilizaram-se 16 cães adultos, machos ou fêmeas, os quais foram d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…In the intraoperative period, continuous lidocaine infusion may be used to decrease myocardial sensitivity to arrhythmias [11,15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the intraoperative period, continuous lidocaine infusion may be used to decrease myocardial sensitivity to arrhythmias [11,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…One hour prior to the beginning of the procedures, a 2-mg/kg lidocaine bolus was administered followed by a continuous 50 µg/kg/min infusion diluted in 0.9% NaCl solution. The isoflurane concentration was adjusted for each animal to maintain an adequate anaesthetic level [10,11].…”
Section: Methodsmentioning
confidence: 99%
“…The results evidenced that FLK decreased cortisol levels in the treated groups in comparison to the control group, which may indicate a reduction in pain-related stress. When observing cardiorespiratory variables after the use of FLK in dogs undergoing arthroscopy, Belmonte et al (2013) found stability in the parameters, evidencing the analgesic action of FLK. Zanella et al (2009) and Rodrigues et al (2012) point out that cortisol is a great marker for assessing both trans-and postsurgical stress.…”
Section: Discussionmentioning
confidence: 88%
“…O isoflurano é o anestésico halogenado mais utilizado na anestesia inalatória de pequenos animais para manutenção anestésica, e foi usado o efeito em conjunto com o uso de bloqueios anestésicos associados a infusão contínua de remifentanfil para analgesia, pois os anestésicos inalatórios, como isoflurano e sevoflurano, não possuem efeitos antinociceptivos (BELMONTE et al, 2013). Durante a manutenção anestésica da paciente do presente relato, foi utilizado isoflurano durante todo o transoperatório.…”
Section: Discussionunclassified